Reflections on the concept of interoperability in information systems - Soares, Delfina de Sá (2014)
Information systems interoperability is one of the main concerns and challenges of information systems managers and researchers, most of whom perceive and approach it on a pure or predominantly technological perspective. In this paper, we argue that a sociotechnical perspective of information systems interoperability should be adopted and we set out seven assertions that, if taken into consideration, may improve the understanding, management, and study of the information systems interoperability phenomenon.